Analisis Kinerja Penyuluh Pertanian Pada Program Upaya Khusus (Upsus) Peningkatan Produksi Padi, Jagung Dan Kedelai Di Kabupaten Aceh Besar - Vivi Suwanti; Suyanti Kasimin; I Ismayani (LPPM Universitas Malikussaleh – Indonesia, 2019)
This research aims to find out (1) the performance of agricultural extension (2) the achievement of rice, corn and soy production on UPSUS and (3) to analyze the relationship between the performance of agricultural extension to the program’s achievement and the relationship of knowledge, skill, motivation, manner, the distance of living place and agricultural facilities with the performance of the agricultural extension. Respondents were taken by using proportional simple random sampling based on Slovin’s. In the other hand, sample of the agricultural extensions were chosen from 2 Sub-district. The data used were primary and secondary data. The data analysis method used was correlation test analysis based on Rank Spearman’s. The research result showed that the performance of agricultural extension was in good range (86,04 %), the achievement of rice, corn and soy production on UPSUS was categorized success (88,07%) and it showed a real relationship between the performance of agricultural extension and the achievement of UPSUS. There was a positive noticeable relationship between knowledge, skill, motivation and manner to the performance of agricultural extension. There was no noticeable relationship between the facilities and the distance of living place.